N-acetylcysteine Counteracts Adipose Tissue Macrophage Infiltration and Insulin Resistance Elicited by Advanced Glycated Albumin in Healthy Rats - da Silva, Karolline S.; Pinto, Paula R.; Fabre, Nelly T.; Gomes, Diego J.; Thieme, Karina; Okuda, Ligia S.; Iborra, Rodrigo T.; Freitas, Vanessa G.; Shimizu, Maria H. M.; Teodoro, Walcy R.; Marie, Suely K. N.; Woods, Tom; et al. (Frontiers in Physiology, 2017)
Background: Advanced glycation endproducts elicit inflammation. However, their role in adipocyte macrophage infiltration and in the development of insulin resistance, especially in the absence of the deleterious biochemical pathways that coexist in diabetes mellitus, remains unknown. We investigated the effect of chronic administration of advanced glycated albumin (AGE-albumin) in healthy rats, associated or not with N-acetylcysteine (NAC) treatment, on insulin sensitivity, adipose tissue transcriptome and macrophage infiltration and polarization. Methods: Male Wistar rats were intraperitoneally injected with control (C) or AGE-albumin alone, or, together with NAC in the drinking water. Biochemical parameters, lipid peroxidation, gene expression and protein contents were, respectively, determined by enzymatic techniques, reactive thiobarbituric acid substances, RT-qPCR and immunohistochemistry or immunoblot. Carboxymethyllysine (CML) and pyrraline (PYR) were determined by LC/mass spectrometry and ELISA. Results: CML and PYR were higher in AGE-albumin as compared to C. Food consumption, body weight, systolic blood pressure, plasma lipids, glucose, hepatic and renal function, adipose tissue relative weight and adipocyte number were similar among groups. In AGE-treated animals, insulin resistance, adipose macrophage infiltration and Col12a1 mRNA were increased with no changes in M1 and M2 phenotypes as compared to C-albumin-treated rats. Total GLUT4 content was reduced by AGE-albumin as compared to C-albumin. NAC improved insulin sensitivity, reduced urine TBARS, adipose macrophage number and Itgam and Mrc mRNA and increased Slc2a4 and Ppara. CD11b, CD206, Ager, Ddost, Cd36, Nfkb1, Il6, Tnf, Adipoq, Retn, Arg and Il12 expressions were similar among groups. Conclusions: AGE-albumin sensitizes adipose tissue to inflammation due to macrophage infiltration and reduces GLUT4, contributing to insulin resistance in healthy rats. NAC antagonizes AGE-albumin and prevents insulin resistance. Therefore, it may be a useful tool in the prevention of AGE action on insulin resistance and long-term complications of DM. Keywords: advanced glycation, adipose tissue, advanced glycated albumin, insulin resistance, diabetes mellitus, macrophage differentiation